Proteomic approaches to profiling of cysteine proteases expressed in leaves and root nodules during natural senescence of the soybean plant - Karumazondo, Rumbidzai Patience (My University, 2011)
Soybean is one of the most cultivated legume plants in developing countries. Nodule senescence is a major limitation in producing high yields of soybean as it coincides with the pod filling stage. Delaying nodule senescence could be a way of increasing the yield of soybean therefore determination of the role of cysteine protease in soybean is of vital importance. In this study, soybean plants were grown under controlled temperature and light conditions. Leaves and root crown nodules were collected at 4, 6, 10, 12 and 16 weeks of age. In a comparative 1-dimensional SDS-PAGE analysis of soybean nodule proteomes as the plant matured, it showed differences in proteins expressed as shown by different banding patterns with less variation between the younger soybean nodule extracts (4, 6 and 10 weeks old) as compared to the older ones (12 and 16 weeks old). As determined by azocasein assay and protease zymography, the protease activity of the nodule extracts generally decreased with an increase in the age of the nodules whereas that of the leaves increased as the plants grew older. Cysteine proteases in the soybean nodule extracts readily cleaved the Z-Arg-Arg-AMC substrate with the highest activity shown in the younger nodules as compared to the older ones. In the leaf extracts, cysteine protease activity increased with age of the leaves. DCG-04, a biotinylated irreversible inhibitor, proved to be an effective label in profiling of activity of cysteine proteases in 1-dimensional and 2-dimensional systems. The labelling was inhibited specifically by cysteine protease inhibitor, E-64. In root nodules, the DCG-04 probing demonstrated that the expression of cysteine proteases is higher in early stages of development of the soybean nodules as compared to the later stages whereas in the leaves, there is higher expression of cysteine proteases in the old leaves (16 weeks). Using 2-dimensional polyacrylamide gel electrophoresis, five cysteine protease isoforms were visualised with the size ranging from approximately 25 to 30 kDa and a pI range of 4-6. In older nodules (12 and 16 weeks old) the higher pI isoforms are down-regulated with the 26 kDa and pI 4.5 protease being the predominant isoform. Affinity precipitation of the cysteine proteases yielded a strong band with the size of about 26 kDa. All assays used show that while in leaves, the expected trend of high expression of cysteine proteases in senescing leaves is observed, in soybean nodules the expression of cysteine proteases decreases with senescence. There is, therefore, no correlation between senescence and cysteine proteases in nodules. The highly expressed cysteine protease in young nodules could play a developmental or regulatory role during the early stages of development.
Thesis (M.Sc. (Biochemistry)) -- University of Limpopo, 2011
Keywords: Soybean plant; Natural senescence; Proteins; Soybean; Plant proteins; Cysteine Proteinases; Neutral proteinases